Ideal liberal subjects and Muslim "Others": liberal nationalism and the racialization of Muslim youth in a progressive Danish school - Jaffe-Walter, Reva (Race, ethnicity and education, 2019)
Drawing on an ethnographic case study of Muslim youth in a Danish lower secondary school, this article explores teacher talk about Muslim immigrant students and how teachers engaged liberal ideals of respect, individualism, and equality in ways that racialized immigrant students. I consider moments of vacillation in teacher talk to explore tensions between teacher's desires to assimilate immigrant students to national norms of belonging and their desires to be perceived as inclusive and 'open.' In doing so, I ask how visions of liberal schooling impose ideas of what a 'normal' citizen should be and how teachers produce 'ideal' liberal subjects in their talk and in the everyday practices of schools. I argue that teachers engage the ideals of abstract liberalism to establish a colorblind discourse of non-racism. While educators described the school as an idealized space where students are encouraged to freely express themselves, to develop unique individual outlooks, it was clear that this vision of 'openness' did not include Muslim students' attachments to religious and cultural identities.